Genealogi Paradigma Fiqh Progresif di Pesantren (Studi Atas Cikal-Bakal Berdirinya Ma'had Aly Al-Qism al-Fiqh di Pondok Pesantren Salafiyah Syafi’iyyah Sukorejo Situbondo): Genealogy of the Progressive Fiqh Paradigm in Islamic Boarding Schools (A Study on the Origins of Ma'had Aly Al-Qism al-Fiqh at Salafiyah Syafi’iyyah Sukorejo Islamic Boarding School, Situbondo) - Pujiono Abd. Hamid (Fenomena, 2014)
Due to the strong tendency toward orthodoxy and orthopraxy, the fiqh tradition in Islamic boarding schools generally moves toward a conservative character and paradigm. Ma'had Aly al-Qism al-Fiqh exhibits a different tendency, showcasing a progressive face and paradigm in the study of Islamic law. This research employs an "intertextual" approach based on both diachronic and synchronic methods. The findings reveal that the genealogy of progressive fiqh at Ma'had Aly can be traced back to the intellectual tradition of Sunni fiqh school leaders (Imams). The paradigm of Sunni Imams, characterized by humility, absence of a priori truth claims, leniency, and flexibility, persists through Sunni educational institutions and traditional teachings conducted by Sunni scholars. Karena kecenderungan yang kuat terhadap ortodoksi dan ortopraksi, tradisi fiqh di pesantren pada umumnya bergerak menuju watak dan paradigma yang konservatif. Ma'had Aly al-Qism al-Fiqh menunjukkan kecenderungan yang berbeda. Ma'had Aly menampilkan wajah dan paradigma yang progresif dalam kajian hukum Islam. Penelitian ini menggunakan pendekatan "intertekstual" berbasis pendekatan diakronik dan sinkronik. Hasilnya menunjukkan bahwa genealogi fiqh progresif di Ma'had Aly dapat ditelusuri hingga tradisi intelektual para Imam mazhab fiqh Sunni. Karakter paradigma Imam Mazhab Sunni yang rendah hati, jauh dari klaim kebenaran a priori, luwes, dan fleksibel, bertahan melalui lembaga-lembaga pendidikan Sunni dan pengajaran tradisional yang dilakukan oleh para ulama Sunni.